Tyrannosaur Canyon - Preston, Douglas J. (Tom Doherty Associates, 2005)
In a post-apocalypse tale, a long-missing moon rock, a killing in a New Mexico canyon, a murderously ambitious scientist, and other factors contribute to the world's greatest scientific discovery.